Player movement requirements and game statistics in elite australian soccer - Burgess, D.; Naughton, G. (Australian Conference of Science and Medicine in Sport and Third National Sports Injury Prevention Conference: 2003. Tackling the barriers of performance and participation, 2003)
Aims: The movement patterns required to play Soccer in elite overseas competitions are well researched. However, no studies have combined analyses of individual player movement rate and game statistics in National Soccer League players in Australia. This project aimed to quantify movement rates and game statistics of elite Australian soccer players. Methods Trak Performance Software was used to analyse movement rate and game statistics via tracking of individual players either in real time with a drawing tablet attached to a laptop computer or retrospectively from video analysis. Forty-five players from the National Soccer League were tracked during competitive games. Analysis included player speed, distance travelled, time in various speed categories, number of sprint efforts, and game-specific statistics. Comparisons were made between defenders (N = 15), midfielders (N = 15) and attackers (N= 15). Data from both 45 minute halves of the game were also compared. Results: Preliminary results showed that midfielders covered more distance (11.9 ± 0.79km) than attackers (8.73 ± 1.13km), and defenders (8.7 ± 0.91km). Midfielders completed the most number of 2 sec maximum speed efforts (15 ± 4.6), have the largest game involvement (68±12.55 actions per game). Player movement speed remained consistent during both halves of games and averaged 7 km/h. The movement patterns of National Soccer Players in Australia are similar to overseas elite level players across field positions. Conclusions: The physical requirements in elite Australian soccer are relatively high. Movement requirements based on a `per minute` demand are similar to AFL. Understanding the demands of on-field movement analysis has significant implications in the periodized program of national soccer league players for whom training is traditionally based on skills.